School-time physical activity among Arab elementary school children in Qatar - Zimmo, Lena (BMC Pediatr, 2017)
BACKGROUND: Recent data from a self-administered questionnaire show that approximately 75% of school children in Qatar do not meet the daily recommended levels of physical activity (PA). Since children spend half of their waking hours in school, it is important to understand when and how much PA children accumulate during the school day. This study aimed to objectively assess school-time PA among elementary school children in Qatar and to determine association of PA with age, gender, body mass index (BMI) status, or day of the week. METHODS: A cross-sectional epidemiological study was conducted in four randomly selected elementary schools in Qatar. Two classes representing grade 1 children (age 5) and grade 4 children (age 9) were randomly selected within each school. A total of 183 elementary school children (86 boys and 97 girls) ages 6–12 years participated in this study. PA was assessed using a three-axial accelerometer (ActiGraph® wGT3X-BT). Participants wore accelerometers on their non-dominant wrist at school (7:00 a.m. to 1:00 p.m.) for five consecutive school days during the week. A cutoff points of 818 counts per 5 s was classified as moderate-to-vigorous physical activity (MVPA). RESULTS: The average duration of MVPA in our study was 28.2 ± 13.5 min per day. Only 39% of participated children reach the recommended school-based MVPA of 30 min or more per day. Students spent on average 58.1 ± 8.4% of school time on sedentary activities. MVPA of boys and girls was similar in age 5 while girls age 9 were less active (23.7 ± 1.5 min/day) than boys of the same age (42.7 ± 1.8 min/day), ES = 0.269, P < 0.001. Neither overweight children nor children at risk for being overweight showed any differences in physical activity parameters when compared to children of normal weight. Our results showed, percentage of MVPA on the first (7.7 ± 5.1%) and last (7.1 ± 4.1%) day of the week was generally lower compared to other weekdays (P < 0.001). CONCLUSION: This was the first study to objectively assess PA during school hours among elementary school-children in Qatar. This study found that many of school children do not perform sufficient time being physically active at school. All students in two age categories (age 5 and age 9) spend the majority of school time engaged in sedentary activities. The low participation of girls age 9 in MVPA is a cause for concern and need to be addressed.